Addressing me in the context of my disease: Why it is so complicated. (January 2023) - Grech, Lisa B
Addressing a person in the context of their disease must be done respectfully. As a person with multiple sclerosis (MS), my preference is to be referred to as such. Some people with MS refer to themselves as MSers, MS warriors, MS sufferers, and that's fine. A person with MS can refer to themselves in the context of their disease in the manner they choose. People without MS should use terminology most respectful and acceptable to the broadest of the minority. Academics sometimes use persons with MS to refer to an infinite number of people. Not only is this incorrect but use of persons has broadly fallen out of favour in recent decades. In this personal viewpoint I discuss these issues from a lived experience perspective.